2006
DOI: 10.1007/s00418-006-0241-y
|View full text |Cite
|
Sign up to set email alerts
|

Laser microdissection combined with immunohistochemistry on serial thin tissue sections: a method allowing efficient mRNA analysis

Abstract: Laser microdissection (LMD) with subsequent reverse transcription-PCR analysis is a powerful histochemical technique subserving the molecular characterization of specific cell types. We developed an efficient method for selective sampling of specific cell populations using immunohistochemistry coupled with LMD. The cerebral cortex of adult rats was cut into serial thin sections. Some sections were immunostained for parvalbumin. The adjacent sections were mounted on Cell Support Film for LMD and stained with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The brain was sliced into 40‐μm coronal sections with Cryotome according to Kase et al (2007). These sections were immunostained for VAChT with essentially the same method as described previously (Tsutsumi et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The brain was sliced into 40‐μm coronal sections with Cryotome according to Kase et al (2007). These sections were immunostained for VAChT with essentially the same method as described previously (Tsutsumi et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Image-assisted RNA and protein analysis: molecular proWling in tissues and cells Laser microdissection has been in use to determine RNA expression in individual cells for some time, and methods have been described to identify and characterize the analyzed cells prior to or concurrent with the RNA analysis (e.g., Kase et al 2007). Two exciting recent reviews report advances in the analysis of cellular RNA and protein proWles which represent giant steps towards the application of these sophisticated techniques to basic and clinical research.…”
Section: Speciwc Applications Of Imagingmentioning
confidence: 99%
“…In parallel analyses, we have confirmed that the majority of directly adjacent sections exhibit equivalent immunostaining for F4/80+ regions of interest when cut at 6 μm. A similar approach has been applied for LCM combined with IHC in brain (Kase et al , 2007). For parallel LCM slides, perform rapid staining as described by Ambion (AM1935 LCM Staining Kit) to provide contrast and for alignment with the identified regions of interest.…”
Section: The Upr and Macrophage Death At The Murine Aortic Rootmentioning
confidence: 99%